Development of age-friendly cities and communities: a case study from the costal belt in Gdańsk - Gębczyńska-Janowicz, Agnieszka; Marczak, Elżbieta; Zapiec, Anna; Grabski, Dawid; Jesionowska, Paulina; Sigmańska, Michaela (Budownictwo i Architektura / Civil and Architectural Engineering, 2026)
The growing proportion of older adults in the population requires modernizing public spaces to better address their needs. Seaside beaches serve as significant recreational areas for seniors, underscoring the importance of evaluating effective design practices in these settings. This study analyzed 11 pedestrian routes in Gdańsk that link public transportation nodes with beach access points. The research area encompassed primary access routes to the seaside zone, pedestrian and cycling paths, and recreational spaces within the districts of Jelitkowo, Przymorze, Brzeźno, Stogi, and Sobieszewo Island. Field observations evaluated the quality of infrastructure in relation to its adaptation for older adults, focusing on beach accessibility, public transport connections, walking route lengths from bus stops to the beach, the quality of small-scale architectural elements such as benches, toilets, and drinking fountains, as well as features of walking trail development related to user safety, including lighting, signage, and architectural barriers. The findings informed the development of guidelines for designing age-friendly coastal urban spaces and highlighted the necessity for continued research in this field.